ASSA14-01-06 One-year outcomes in Chinese patients with acute coronary syndromes: a subanalysis of EPICOR Asia study. (1st December 2014) - Huo, Y; Han, YL; Ge, JB; Chen, JY; Yuan, ZY; Qiao, SB; Yu, B
Abstract : Objectives: The outcomes of Chinese patients with acute coronary syndromes (ACS) remain unclear. This study aimed to investigate the 1-year outcomes of Chinese patients with ST segment elevation myocardial infarction (STEMI), non-STEMI (NSTEMI) and unstable angina (UA). Methods: This is a subanalysis of Long-tErm follow-uP of antithrombotic management patterns In Acute CORonary Syndrome patients in Asia (EPICOR Asia) study (NCT01361386 ), a prospective, multinational, observational study on ACS patients after discharge with 2-year follow-up. One-year follow-up outcomes of Chinese patients with ACS were reported based on the final diagnosis of STEMI, NSTEMI or UA, which were confirmed by an independent validation committee. Results: Eight thousand two hundred and fourteen Chinese patients with ACS were finally included in this study (STEMI, n = 3961; NSTEMI, n = 1315; UA, n = 2938). The baseline characteristics of patients were reported in Table 1 . The one-year incidences of cardiovascular/cerebrovascular event (20.5%), congestive heart failure (2.1%), primary ischaemic stroke (1.4%), and death (3.7%) were highest in patients with NSTEMI (overall p < 0.01 vs STEMI) (Table 2 ). Additionally, the mortality of patients with UA was significantly lower than that of STEMI patients (p < 0.001). The one-year incidence of bleeding event is the same in STEMI and NSTEMI patients. The accumulated mortality in patients with STEMI, NSTEMI and UA all increased with one year follow-up (Figure 1 ). Conclusion: The outcomes of Chinese patients with NSTEMI were poorer than that of STEMI and UA. Therefore, further studies are needed to identify ideal therapeutic algorithm for these patients in China.